Studi Literatur: Tingkat, Penyebab Dan Strategi Pencegahan Dehidrasi Pada Remaja Dan Dewasa Muda - Rainiah Az'zahra, Aliza; Nur Hanifa, Anestia; Sampurna, Jaya; Febrian, Rifky; Khoirunnisa, Salma; Sukma Ayu, Desi; Dwi Santiawati, Isma; Flora Purba, Sindi; Nurul Azizah, Sabrina; Syahdina Putri, Tyas; Sopiah, Popi; Ridwan, Heri (Universitas Haji Sumatera Utara, 2025)
Dehydration is a common health problem among adolescents and young adults, with a high prevalence that can impair physical and cognitive functioning. Research shows that many individuals do not meet the recommended daily fluid requirements, which contributes to the risk of dehydration. Several factors such as the habit of consuming water only when thirsty, inadequate nutritional status, low physical activity, and obesity, play an important role in the incidence of dehydration. This study uses a literature review method that analyzes various related articles and studies, the results of the Publish or Perish search on the Google Scholar database using the keywords “dehydration, young adults, dehydration factors, prevention, adolescents” from 2016-2024 there are 89 journals, after being analyzed there are 10 journals that contain dehydration, young adults, dehydration factors, prevention, adolescents. The results show that education and counseling on the importance of adequate fluid intake is an effective solution. Educational programs in educational institutions and collaboration between health and non-health students can increase awareness and healthy fluid consumption habits. In addition, creating an environment that supports easy access to clean water is essential. Systematic and data-driven prevention efforts are expected to reduce the incidence of dehydration and improve overall health among adolescents and young adults.